Breslow Intermediates (Amino Enols) and Their Keto Tautomers: First Gas‐Phase Characterization by IR Ion Spectroscopy. Issue 8 (1st December 2020) - Paul, Mathias; Peckelsen, Katrin; Thomulka, Thomas; Martens, Jonathan; Berden, Giel; Oomens, Jos; Neudörfl, Jörg‐M.; Breugst, Martin; Meijer, Anthony J. H. M.; Schäfer, Mathias; Berkessel, Albrecht
Abstract: Breslow intermediates (BIs) are the crucial nucleophilic amino enol intermediates formed from electrophilic aldehydes in the course of N‐heterocyclic carbene (NHC)‐catalyzed umpolung reactions. Both in organocatalytic and enzymatic umpolung, the question whether the Breslow intermediate exists as the nucleophilic enol or in the form of its electrophilic keto tautomer is of utmost importance for its reactivity and function. Herein, the preparation of charge‐tagged Breslow intermediates/keto tautomers derived from three different types of NHCs (imidazolidin‐2‐ylidenes, 1, 2, 4‐triazolin‐5‐ylidenes, thiazolin‐2‐ylidenes) and aldehydes is reported. An ammonium charge tag is introduced through the aldehyde unit or the NHC. ESI‐MS IR ion spectroscopy allowed the unambiguous conclusion that in the gas phase, the imidazolidin‐2‐ylidene‐derived BI indeed exists as a diamino enol, while both 1, 2, 4‐triazolin‐5‐ylidenes and thiazolin‐2‐ylidenes give the keto tautomer. This result coincides with the tautomeric states observed for the BIs in solution (NMR) and in the crystalline state (XRD), and is in line with our earlier calculations on the energetics of BI keto–enol equilibria. Abstract : Breslow intermediates in the gas phase : In N ‐heterocyclic carbene (NHC)‐catalyzed Umpolung, the reaction of the substrate aldehyde with the NHC gives the Breslow intermediate (BI) as pivotal species. The combination of IR ion spectroscopy with quantum chemical computations can determine whether the BI exists as a nucleophilic amino enol or as its keto tautomer in the gas phase, which is decisive for its reactivity both in enzymatic catalysis and in organocatalysis.